2010
DOI: 10.1210/jc.2010-0644
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide Treatment in Aggressive Pituitary Tumors and Pituitary Carcinomas: A French Multicenter Experience

Abstract: Temozolomide treatment may be an effective option for some aggressive pituitary tumors or carcinomas. Response to a trial of three cycles of treatment seems sufficient to identify responders and more reliable than patient MGMT status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
145
3
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(162 citation statements)
references
References 24 publications
10
145
3
4
Order By: Relevance
“…The alkylating compound, temozolomide, recently demonstrated a significant response against aggressive pituitary adenomas and carcinomas (19,37,38). A recent relatively large cohort study (nZ24) (19) demonstrated that immunohistochemically low MGMT expression predicts a better response to temozolomide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alkylating compound, temozolomide, recently demonstrated a significant response against aggressive pituitary adenomas and carcinomas (19,37,38). A recent relatively large cohort study (nZ24) (19) demonstrated that immunohistochemically low MGMT expression predicts a better response to temozolomide.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have argued that an immunohistochemical MGMT expression analysis is not clinically useful in predicting tumor responses to temozolomide therapy (20,37,38). One possible explanation of the controversy is the acquisition of temozolomide resistance due to the loss of MSH6 expression during temozolomide treatments (19,20,39).…”
Section: Discussionmentioning
confidence: 99%
“…In our series, TMZ was successfully used in two carcinomas and a highly aggressive prolactinoma. Tumors showing reduced methylguanine-DNA methyltransferase expression may be more sensitive to TMZ (41), but this finding is debatable and a 3-month trial is generally able to identify TMZ responders (42). Observational data on early chemotherapy associated with longlasting responses in pituitary carcinomas (39) support the need for an early recognition of their metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
“…1%) are rare entities of pituitary tumours (Saeger et al 2007). Medical treatment regimens with dopamine agonists and somatostatin analogues are established for prolactinomas and somatotropinomas respectively (Colao & Savastano 2011, Giustina et al 2011, and promising treatment results with temozolomide have been reported in a few cases of pituitary carcinoma (Raverot et al 2010). The other pituitary adenoma types as well as drug-resistant prolactinomas and somatotropinomas have to be removed by transsphenoidal or transcranial surgery.…”
Section: Introductionmentioning
confidence: 99%